Tensegrity Metamaterials: Toward Failure‐Resistant Engineering Systems through Delocalized Deformation - Bauer, Jens; Kraus, Julie A.; Crook, Cameron; Rimoli, Julian J.; Valdevit, Lorenzo (Advanced materials (Weinheim), 2021)
Failure of materials and structures is inherently linked to localized mechanisms, from shear banding in metals, to crack propagation in ceramics and collapse of space‐trusses after buckling of individual struts. In lightweight structures, localized deformation causes catastrophic failure, limiting their application to small strain regimes. To ensure robustness under real‐world nonlinear loading scenarios, overdesigned linear‐elastic constructions are adopted. Here, the concept of delocalized deformation as a pathway to failure‐resistant structures and materials is introduced. Space‐tileable tensegrity metamaterials achieving delocalized deformation via the discontinuity of their compression members are presented. Unprecedented failure resistance is shown, with up to 25‐fold enhancement in deformability and orders of magnitude increased energy absorption capability without failure over same‐strength state‐of‐the‐art lattice architectures. This study provides important groundwork for design of superior engineering systems, from reusable impact protection systems to adaptive load‐bearing structures. Failure of materials and structures is typically preceded by a catastrophic chain reaction of locally confined damage events, while large parts of the system do not experience critical loads. Breaking with this established paradigm, this study introduces the concept of delocalized deformation, enabling failure‐resistant structures and materials via 3D tensegrity metamaterials.